Bringing health into transportation and land use scenario planning: Creating a National Public Health Assessment Model (N-PHAM). (September 2018) - Schoner, Jessica; Chapman, Jim; Brookes, Allen; MacLeod, Kara E.; Fox, Eric H.; Iroz-Elardo, Nicole; Frank, Lawrence D.
Abstract: There is mounting evidence linking land development and transportation investments to physical activity with resulting implications for chronic disease prevention. Links between the physical environment and health have traditionally focused on harmful exposures such as air pollution, noise, and traffic injury. Given limited funds and competition for how and where investments are made, there is a need to prioritize and target resources to maximize health benefits that can include activity related chronic disease prevention. The ability to apply this evidence to decision making has been limited by the complexity and inconsistency of research methods, and lack of a direct connection with the planning contexts in which decisions are made. Scenario planning tools provide a method to apply evidence with spatial planning decisions at a range of geographic scales. The US Environmental Protection Agency commissioned the development of a National Public Health Assessment Model (N-PHAM). This project utilized built and natural environment data at the block-group level and large population surveys to model the relationships of the environment with several health outcomes for a range of age and income groups. N-PHAM is the first health assessment tool that can connect to multiple existing scenario planning platforms utilizing nationally available data and can be consistently applied nationally. Such tools can empower communities to choose investments that have the greatest potential to improve public health and quality of life, reduce health care costs, and address environmental justice related disparities. Highlights: A health assessment software tool was developed to evaluate land and transportation planning decisions. Models were developed using travel behavior and health surveillance data on large surveys spatially linked with built environmental data. Health related outcomes are tied to both built and natural environment features. Environmental patterns for walking were associated with lower body mass index and obesity prevalence. Employment land use and accessibility were associated with walking for transportation. City planners have used this health assessment tool to inform transportation investments to promote health.